MARKETING STRATEGY ANALYSIS TO IMPROVE COMPETITIVENESS BAZNAS AND LAZNAS - Muhammad Furqan MD; Muhammad Zen (Advances In Social Humanities Research, 2023)
The marketing mix is a set of factors that are controlled to affect the demand for the company's output. An extraordinary combination suitable for making consumers aware of the company's products Companies using a marketing mix strategy with a mix of different elements Grouping The elements of the marketing mix are product (product), price (gift), location (location) and promotion (advertisement) ) According to LAZ NO law .23 of 2011 to Zakat Management said this: "Amil Zakat Institution, hereinafter abbreviated as LAZ is an established institution for people with the obligation to help collect, distribute and use zakat". Competitive advantage has differences. Competitive advantage is the total price vs competition, which attracts more customers. The complete offer must be more attractive offered by competitors to create a competitive advantage. The idea of the initial stage of this research is to determine First, the observed and examined objects and observations made on predetermined observable objects, commitment to identify potential problems of observable objects. The sampling technique used in this study was an expert sample, which is an example of the benefits of a sample included in the non-probability category, as exemplified. PKPU and Rumah Zakat digital marketing strategies are integrated digital marketing methods. PKPU and Rumah Zakat use all digital components to the maximum and creative and innovative human resources get partnerships in the form of an extensive internet web environment and in information dissemination. The digital marketing strategy is very effective in collecting and distributing PKPU community funds and Rumah Zakat. This can be seen from the collection and distribution of ZIS funds from 2012 to 2017.